2021
DOI: 10.1111/aphw.12249
|View full text |Cite
|
Sign up to set email alerts
|

Congruence and discrepancy in migrant children’s and mothers’ perceived discrimination: Using response surface analysis to examine the effects on psychological distress

Abstract: New migrants from Mainland China to Hong Kong have faced increased discrimination from local Hong Kongers, which may have negative impacts on their adjustment and mental health. Guided by the family systems theory, we tested the dyadic effects of perceived discrimination levels among migrant children and mothers on their psychological distress in a sample of 200 child–mother pairs who migrated from Mainland China to Hong Kong. Using polynomial regression and response surface analyses, we found that when childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Second, although we included multi-informant reports from parents and children on child internalizing and externalizing behaviors, perceived discrimination and theory of intelligence were only measured from the perspective of the child. A recent study found that discrepancy in parent and child reports of discrimination in Chinese migrants, where children reported higher levels of perceived discrimination, was associated with increased psychological distress for children (Qu et al, 2021). Studies have also identified a discrepancy between parent and child reports of personality and self-rated intelligence (e.g., Wirthwein et al, 2019).…”
Section: Study Limitationsmentioning
confidence: 99%
“…Second, although we included multi-informant reports from parents and children on child internalizing and externalizing behaviors, perceived discrimination and theory of intelligence were only measured from the perspective of the child. A recent study found that discrepancy in parent and child reports of discrimination in Chinese migrants, where children reported higher levels of perceived discrimination, was associated with increased psychological distress for children (Qu et al, 2021). Studies have also identified a discrepancy between parent and child reports of personality and self-rated intelligence (e.g., Wirthwein et al, 2019).…”
Section: Study Limitationsmentioning
confidence: 99%
“…Third, this study only examined child-mother congruence in the family context and its association with depressive symptoms at the microlevel through a dyadic prism. Future research, using a multisystemic perspective, should explore child-mother congruence in relation to other factors at multiple levels, such as testing how congruence in perceived discrimination from the ecosystem contributes to psychological distress in child-mother dyads (Qu et al, 2021).…”
Section: Limitationsmentioning
confidence: 99%
“…This special issue tackles this research gap by offering ground‐breaking insights into migrant health, including psychological (e.g. depression, social anxiety, externalizing problems, and subjective well‐being; Këllezi et al, 2021*; Li, Su, et al, 2021*; Qu et al, 2021*) and physical (e.g. sleep disturbances; Zhang & Wang, in press*) health among diverse populations of migrants (e.g.…”
mentioning
confidence: 99%
“…Accordingly, the special issue tackles important individual (e.g. perceived discrimination, job stress; Li, Du, et al, 2021*; Qu et al, 2021*; Xie et al, 2020*) and interpersonal (e.g. parental control, negative peer interactions, single or partnered relationship status; Adamczyk et al, 2021*; Li, Su, et al, 2021*) predictors of migrant health using multiple research designs (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation